Airspaces-derived exosomes contain disease-relevant protein signatures in a mouse model of cystic fibrosis (CF)-like mucoinflammatory lung disease - Yun Mao; Amol Suryawanshi; Sonika Patial; Yogesh Saini (Frontiers Media S.A., 2024)
Exosomes, membrane-bound extracellular vesicles, ranging from approximately 30-200 nm in diameter, are released by almost all cell types and play critical roles in intercellular communication. In response to the prevailing stress, the exosome-bound protein signatures vary in abundance and composition. To identify the bronchoalveolar lavage fluid (BALF) exosome-bound proteins associated with mucoinflammatory lung disease and to gain insights into their functional implications, we compared BALF exosomes-derived proteins from adult Scnn1b transgenic (Scnn1b-Tg+) and wild type (WT) mice. A total of 3,144 and 3,119 proteins were identified in BALF exosomes from Scnn1b-Tg+ and WT mice, respectively. Using cutoff criteria (Log2 fold-change > 1 and adjusted p-value < 0.05), the comparison of identified proteins revealed 127 and 30 proteins that were significantly upregulated and downregulated, respectively, in Scnn1b-Tg+ versus WT mice. In addition, 52 and 27 proteins were exclusively enriched in Scnn1b-Tg+ and WT mice, respectively. The identified exosome-bound proteins from the homeostatic airspaces of WT mice were mostly relevant to the normal physiological processes. The protein signatures enriched in the BALF exosomes of Scnn1b-Tg+ mice were relevant to macrophage activation and mucoinflammatory processes. Ingenuity pathway analyses revealed that the enriched proteins in Scnn1b-Tg+ mice contributed to the inflammatory responses and antimicrobial defense pathways. Selective proteins including, RETNLA/FIZZ1, LGALS3/Galectin-3, S100A8/MRP8, and CHIL3/YM1 were immunolocalized to specific cell types. The comparative analysis between enriched BALF exosome proteins and previously identified differentially upregulated genes in Scnn1b-Tg+ versus WT mice suggested that the compartment-/cell-specific upregulation in gene expression dictates the enrichment of their respective proteins in the lung airspaces. Taken together, this study demonstrates that the BALF exosome-bound protein signatures reflect disease-relevant disturbances. Our findings suggest that the exosomes carry disease-relevant protein signatures that can be used as a diagnostic as well as predictive biomarkers for mucoinflammatory lung disease.